Efficient Cell-Wall Disruption of Microalgae Chlorella Vulgaris in water by catalytic ozonation over Microporous Carbon-Supported Titanium Oxide - Rame Rame; Nilawati Nilawati; Silvy Djayanti; Novarina Irnaning Handayani; Agus Purwanto; Lisa Ruliaty; Ganang Dwi Harjanto (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2018)
This study investigated several parameters for cell-wall disruption from microalgae Chlorella vulgaris during catalytic ozonation over microporous carbon-supported titanium oxide, including flow ozone, catalytic time, and reactor capacity. At the same time, the cell-wall disruption yield and an active compound yield such as chlorophyll and carotenoid were evaluated for each pretreatment. The required delivered flow ozone to achieve 76,47% cell-wall disruption of Chlorella vulgaris was 1 minute at 4 LPM, which produced chlorophyll 56,75% and carotenoid 89,09%. Carbon-supported titanium oxide reduces the required O3 dose and catalytic time for cell-wall disruption; however, it limited chlorophyll yield did not exceed 75,67%. Pretreatment with 1 minute at 1 LPM in 2 liters produced carotenoid yield by approximately 98,18%, though it reduced chlorophyll to 59,45%.